THE EFFECT OF ENVIRONMENTAL INVESTMENT AND FIRM ENVIRONMENTAL PERFORMANCE ON FIRM VALUE: AN EMPIRICAL STUDY IN INDONESIA - Dhiona Ayu Nani; Vera Apri Dina Safitri; Lindrianasari Lindrianasari (Journal of Applied Finance & Accounting, 2022)
This study examines the effect of environmental investment and firm environmental performance on firm value. The method used is a quantitative method with secondary data. This study used panel data from firms' financial statements sensitive to environmental issues. The sample was companies sensitive to environmental issues, such as mining, plantation, and manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2014-2017. The results of this study indicate that investment in the environmental sector and firm environmental performance have a positive but not significant effect on firm value. This result shows that the investment in environmental conservation conducted by companies was effective for improving the firm value but not significant; this is because the investment in the environmental sector companies spend in Indonesia is still minimal. The results of this study also show that environmental performance has a positive but insignificant effect; this is because, based on existing data, not many companies in Indonesia have received gold and green ratings. The implications of this study are (a) the company's efforts in preserving the environment because their business activities are not only beneficial for the surrounding society, but this will improve the firm's environmental performance and sustainability, and (b) investment in the environmental sector is essential for companies to achieve good environmental performance, and (c) for accounting standard setters (IAI) and the Government, more binding rules are needed for companies to disclose the costs of environmental conservation.